The Real Wage-Employment Relationship in the United States - Nickell, Stephen; Symons, James (Journal of Labor Economics, 1990)
This article examines the real wage-employment relationship in the United States in the light of the diversity of results in the literature. It demonstrates that, when the relationship is correctly specified, in the sense that due allowance is made for technical progress and capital accumulation, and the appropriate value-added deflator is used for the wage, then a negative relationship may be observed in the data. An incorrect specification, however, is as likely to lead to a positive relationship as a negative one.